2020
DOI: 10.1177/0963662520960663
|View full text |Cite
|
Sign up to set email alerts
|

Social participation in science: Perspectives of Spanish civil society organizations

Abstract: There is a general trend toward more active, broader, and more inclusive participation of different stakeholders in science. Civil society organizations’ inclusion in the scientific process is being promoted. However, there are few attempts to understand the role of civil society organizations in research. This study is based on the analysis of 31 semi-structured interviews with Spanish civil society organization managers and representatives. Our main results regarding the current relationship between civil so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Volunteers are essential for the functioning of each group, but their lack of commitment in certain moments of organizational life is well known [Llorente, Revuelta and Carrió, 2021]. Offering training, challenges, and a feeling of accomplishment is the best way to retain them, as has been indicated by some of the successful experiences in museums and schools [Castellanos, Munilla and Sprünker, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Volunteers are essential for the functioning of each group, but their lack of commitment in certain moments of organizational life is well known [Llorente, Revuelta and Carrió, 2021]. Offering training, challenges, and a feeling of accomplishment is the best way to retain them, as has been indicated by some of the successful experiences in museums and schools [Castellanos, Munilla and Sprünker, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…CSOs can generally be defined as non-governmental actors, varying from activists, small community-based groups and informal movements to highly organized institutions and international organizations or networks [ 12 ]. One common goal of CSOs is to participate in or influence (health) policy [ 13 , 14 ] and research [ 15 ] on behalf of citizens or socially and economically disadvantaged groups, for example, women, persons with disabilities or migrants [ 16 ]. Due to their independence from direct governmental management, their non-economic aims and their voluntary and bottom-up way of working [ 11 ], PAOs and CSOs have much in common.…”
Section: Patient Advocacy Organizationsmentioning
confidence: 99%
“…Some of these initiatives emerge from problems identified by communities or CSOs, often related to environmental issues of pollution, health hazards, species conservation, water and air quality, or draining of natural resources [Brulle and Pellow, 2006;Leung, Yen and Minkler, 2004;Macey et al, 2014]. However, previous studies have revealed that Spanish CSOs mainly participate in science within one single research moment and that they are unaware of their own potential [Llorente, Revuelta and Carrió, 2021]. Even though these initiatives emerge from outside scientific institutions, they rely on scientific procedures for collecting, validating, analysing and interpreting data [Macey et al, 2014;Ottinger, 2010], and scientific content is often co-produced between professional scientists and citizens [Kullenberg and Kasperowski, 2016].…”
Section: Stakeholders Involvement In Citizen Participation In Sciencementioning
confidence: 99%